Payday Lending in Canada in a Global Context A Mature Industry with Chronic Challenges (Springer International Publishing, 2018)
This book analyzes the highly contentious payday lending industry, presenting valuable new data collected during Canada's recent regulatory reviews and demonstrating its relevance to payday lending conversations taking place worldwide. The authors treat the industry with a balanced hand by establishing its importance as an example of financialization and acknowledging the complex impact of payday lending services on low-income and credit-constrained clients. Up-to-date data from an interdisciplinary mix of financial, econometric, legal, behavioral economic, and socioeconomic sources-all in the context of an established Canadian industry-provide both proponents and opponents of payday lending with valuable evidence for their discussions of how much regulation is required to minimize harmful consequences. These insights from Canada expand a US-centric conversation and provide a key resource for the growing list of countries in which the industry is present, from the UK and Poland to South Africa and Australia.